Economic development and environmental history in the Anthropocene perspectives on Asia and Africa - Austin, Gareth ([London] [Bloomsbury Academic], 2019)
"For the populations of the developing economies - the vast majority of humanity - the present century offers the prospect of emulating Western standards of living. This hope is combined with increasing awareness of the environmental consequences of the very process of global industrialisation itself. This book explores the interactions between economic development and the physical environment in four regions of the developing world: Sub-Saharan Africa, South Asia, Southeast Asia and East Asia. The contributors focus on the 'Anthropocene': our present era, in which humanity's influence on the physical environment has begun to mark the geological record.

Economic Development and Environmental History in the Anthropocene examines environmental changes at global level and human responses to environmental opportunities and constraints on more local and regional scales, themes which have been insufficiently studied to date. This volume fills this gap in the literature by combining historical, economic and geographical perspectives to consider the implications of the Anthropocene for economic development in Asia and Africa"--
1.Introduction (Gareth Austin, Cambridge University, UK)
2. Environmental Impacts of Colonial Dynamics, 1400-1800: Ecological Imperialism Versus Ecological Adaptation (Amélia Polónia, University of Porto, Portugal)
3. Agricultural Systems in Sub-Saharan Africa 1500-1800 (Mats Widgren, Stockholm University, Sweden)
4. Containerization, Energy and the Anthropocene in West Africa (Emily Osborn, University of Chicago, USA)
5. Africa and the Anthropocene (Gareth Austin, Cambridge University, UK)
6. Local Resource Constraints, Regional Trade and Environmental Sustainability: An Asian Historical Perspective (Kaoru Sugihara, National Graduate Institute for Policy Studies in Tokyo, Japan)
7. Forests and a New Energy Economy in 19th-Century South India (Prasannan Parthasarathi, Boston College, USA)
8. Land Quality, Carrying Capacity and Sustainable Agricultural Change in 20th-Century India (Tirthankar Roy, LSE, UK)
9. Forest Development in Southeast Asia and the Human Factor, 1500-2000 (Peter Boomgaard, University of Amsterdam, the Netherlands)
10. Developing the Rainforest: Rubber, Environment and Economy in Southeast Asia (Corey Ross, University of Birmingham, UK)
11. The Development of Energy Conservation Technology in Japan, 1920-70: An Analysis of Energy-Intensive Industries and Energy Conservation Policies (Satoru Kobori, Nagoya University, Japan)
12. The Development of South Korea's Nuclear Energy Industry in a Resource- and Capital-Scarce Environment (Se Young Jang, Graduate Institute of International and Development Studies, Geneva, Switzerland)
13. Water, Energy, and Politics: Chinese Industrial Revolutions in Global Environmental Perspective (Kenneth Pomeranz, University of Chicago, USA)
14. The Present Climate of Economic History (Julia Adeney Thomas, University of Notre Dame, USA)
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects -- Africa, Sub-Saharan.; Economic development -- Environmental aspects -- Asia; Human ecology -- Africa, Sub-Saharan -- History; Human ecology -- Asia -- History